1984
DOI: 10.1149/1.2115751
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Selenide Photoelectrodes: Efficient Radiative Recombination in a Stable Photoelectrochemical Cell

Abstract: Photoluminescence (PL) and electroluminescence (EL) from single-crystal, n-type, Al-doped ZnSe (ZnSe:A1) electrodes have been studied. These samples exhibit both edge emission (k~a~ ~ 460 nm) and subbandgap emission when excited at several ultrabandgap wavelengths. The latter PL band is particularly intense, with a measured radiative quantum yield of -10 -I to 10-~; the transition appears to be at least partially self-activated (SA) in origin, based on previously reported PL data. Excited-state communication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…We show that PL intensity from the modified electrode is in good accord with a dead-layer model found applicable to naked, homogeneous electrodes (4,7,8), and that EL properties of the modified CdSe electrode are comparable to those of the naked electrode. We show that PL intensity from the modified electrode is in good accord with a dead-layer model found applicable to naked, homogeneous electrodes (4,7,8), and that EL properties of the modified CdSe electrode are comparable to those of the naked electrode.…”
Section: Luminescent Properties Of a Surface-modified Cadmium Selenidsupporting
confidence: 77%
See 1 more Smart Citation
“…We show that PL intensity from the modified electrode is in good accord with a dead-layer model found applicable to naked, homogeneous electrodes (4,7,8), and that EL properties of the modified CdSe electrode are comparable to those of the naked electrode. We show that PL intensity from the modified electrode is in good accord with a dead-layer model found applicable to naked, homogeneous electrodes (4,7,8), and that EL properties of the modified CdSe electrode are comparable to those of the naked electrode.…”
Section: Luminescent Properties Of a Surface-modified Cadmium Selenidsupporting
confidence: 77%
“…In this report, we examine PL and EL properties of a ferri/ferrocyanide-modified n-CdSe electrode. We show that PL intensity from the modified electrode is in good accord with a dead-layer model found applicable to naked, homogeneous electrodes (4,7,8), and that EL properties of the modified CdSe electrode are comparable to those of the naked electrode.…”
Section: Luminescent Properties Of a Surface-modified Cadmium Selenid...supporting
confidence: 77%
“…Since the 1960s, electrochemical luminescence ͑ECL͒ of semiconductors in liquid electrolyte has been intensively investigated [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and it was shown that there are two types of ECL of n-type semiconductors. 1,4,10 One is observed under cathodic polarization and its luminescence originates from the recombination of electronhole pairs with the aid of hole injection to the valence band of semiconductors by the oxidative electrolyte ͑e.g., S 2 O 8 2− or ͓Fe͑CN͒ 6 ͔ 3− ͒.…”
mentioning
confidence: 99%
“…Although the studies described thus far have utilized edge emission, we have examined one PEC, constiucted from an n-ZnSe:Al electrode and stabilizing diselenide or ditelluride electrolyte, for which subbar Iagap P. was used for character-" ization (104). Figure 21 shows that n-ZnSe:AI ele<tu,.…”
Section: *"mentioning
confidence: 99%